Experimental and computational studies of fatty acid distribution networks. Issue 11 (13th November 2015) - Liu, Yong; Buendía-Rodríguez, Germán; Peñuelas-Rívas, Claudia Giovanna; Tan, Zhiliang; Rívas-Guevara, María; Tenorio-Borroto, Esvieta; Munteanu, Cristian R.; Pazos, Alejandro; González-Díaz, Humberto
<x xml:space="preserve">Abstract</x> A new PT-LFER model is useful for predicting a distribution network in terms of specific fatty acid distribution.